Respostas
respondido por:
11
∫
Fazendo (e^2t + 2) = u
ficamos:
u = e^2t + 2
entao ficamos:
∫
1/2*∫
Integral de uma potencia:
∫u^(1/3)du = u^(1/3 +1)/(1/3+1)
............... = u^(1/3 +3/3)/(1/3+3/3)
............... = u^(4/3)/4/3)
Entao vai ficar:
1/2*U^(4/3)/(4/3)
1/2*U^(4/3)*(3/4) ← Passa invertido
1/2*3/4*U^(4/3)
3/8*U^(4/3)
Agora só substituir "U" = (e^2t + 2)
Logo, ficara:
3/8*(e^2t + 2)^(4/3) + K
Fazendo (e^2t + 2) = u
ficamos:
u = e^2t + 2
entao ficamos:
∫
1/2*∫
Integral de uma potencia:
∫u^(1/3)du = u^(1/3 +1)/(1/3+1)
............... = u^(1/3 +3/3)/(1/3+3/3)
............... = u^(4/3)/4/3)
Entao vai ficar:
1/2*U^(4/3)/(4/3)
1/2*U^(4/3)*(3/4) ← Passa invertido
1/2*3/4*U^(4/3)
3/8*U^(4/3)
Agora só substituir "U" = (e^2t + 2)
Logo, ficara:
3/8*(e^2t + 2)^(4/3) + K
deividsilva784:
Espero ter ajudado: :)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás